The Meaning of Life and Work-Life Balance of Women Dual Roles in City X - Mardiyanti, Ressy; Purwaningtyas, Fifin Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The aim of this research is to find out how meaning of life influences work-life balance among women with dual roles in Surabaya. Fulfilling the needs of the family today is not only done by men, but many women also help in this matter, and what they do is work. Working is everyone's dream, but for women working has various problems and fatigue which will affect their physical and psychological condition, because they have a dual role in their lives, namely a housewife whose main task is to care for and care for her family, and her secondary role as a worker in the workplace. a company. Both roles must be carried out well to create balance. Worklife balance will help working women to be better able to adapt to various changes. Worklife balance can be achieved if someone really enjoys their role and has a good meaning in carrying it out. A woman who can enjoy her various roles in life and is able to manage her various activities well will achieve a good life balance as well. This research is quantitative research with a purposive sampling technique or based on certain characteristics. Researchers used parametric statistical analysis techniques with simple regression tests and assisted with processing using SPSS 23 statistical software. Obtained significance results of 0.000 < 0.05, with a comparison of the calculated t value with the t table of 5.505 > 1.960, which means there is an influence between the meaning of life on work life balance among women with dual roles in Surabaya. The meaning of life variable contributes an influence of 13.8% to work life balance. It is hoped that through this research the government and industry agencies in making regulations or policies can pay attention to this factor.Tujuan dari penelitian ini yakni guna menguji dampak makna hidup terhadap work-life balance pada perempuan yang mempunyai peran ganda di Surabaya. Saat ini, baik laki-laki maupun perempuan berkontribusi dalam memenuhi kebutuhan keluarga, dan perempuan secara aktif berpartisipasi dalam dunia kerja. Bekerja adalah cita-cita universal, namun perempuan menghadapi tantangan dan kelelahan unik yang dapat berdampak pada kesejahteraan fisik dan mental mereka. Hal ini disebabkan oleh peran ganda mereka selaku ibu rumah tangga, mempunyai tanggung jawab atas pemeliharaan serta kesejahteraan keluarga, serta profesional di tempat kerja. Sebuah perusahaan. Kedua peran itu harus bisa dijalankan dengan baik agar tecipta keseimbangan. Worklife balance akan membantu Wanita bekerja untuk bisa lebih baik dalam beradaptasi dengan berbagai perubahan. Worklife balance bisa tercapai apabila seseorang benar-benar menikmati perannya dan memiliki kebermaknaan yang baik dalam menjalankannya. Seorang wanita yang dapat memperoleh kesenangan dari beragam tugas hidupnya dan secara efektif menangani berbagai pekerjaannya akan mencapai keseimbangan hidup yang harmonis. Penelitian ini memakai pendekatan penelitian kuantitatif dengan memanfaatkan teknik sampel purposif untuk memilih partisipan berdasarkan karakteristik tertentu. Peneliti menggunakan teknik analisis statistic parametrik dengan uji regresi sederhana dan dibantu pengolahannya menggunakan software statistic SPSS 23. Didapatkan capaian signifikansi sebesar 0,000 < 0,05, dengan perbandingan nilai t hitung dengan t table sebesar 5,505 > 1,960, yang artinya ada pengaruh antara meaning of life pada work life balance pada wanita peran ganda di Surabaya. Variable meaning of life memberikan kontribusi pengaruh sebesar 13.8% terhadap work life balance. Diharapkan melalui penelitian ini pemerintah maupun instansi industry dalam pembuatan aturan ataupun kebijakan dapat memperhatikan faktor ini.